Adaptation strategies and neurophysiological response in early-stage Parkinson's disease: BioVRSea approach - Jacob, Deborah; Guerrini, Lorena; Pescaglia, Federica; Pierucci, Simona; Gelormini, Carmine; Minutolo, Vincenzo; Fratini, Antonio; Di Lorenzo, Giorgio; Petersen, Hannes; Gargiulo, Paolo (Frontiers in Human Neuroscience, 2023)
There is accumulating evidence that many pathological conditions affecting human balance are consequence of postural control (PC) failure or overstimulation such as in motion sickness.Our research shows the potential of using the response to a complex postural control task to assess patients with early-stage Parkinson's Disease (PD). We developed a unique measurement model, where the PC task is triggered by a moving platform in a virtual reality environment while simultaneously recording EEG, EMG and CoP signals. This novel paradigm of assessment is called BioVRSea. We studied the interplay between biosignals and their differences in healthy subjects and with early-stage PD. Despite the limited number of subjects (29 healthy and 9 PD) the results of our work show significant differences in several biosignals features, demonstrating that the combined output of posturography, muscle activation and cortical response is capable of distinguishing healthy from pathological. The differences measured following the end of the platform movement are remarkable, as the induced sway is different between the two groups and triggers statistically relevant cortical activities in α and θ bands. This is a first important step to develop a multi-metric signature able to quantify PC and distinguish healthy from pathological response.